The use of Prohibited Substances in Playing Games: With special reference to Asian Games - Wickramaratne, P.D.Vimuckthi Charika (International Journal of Management Excellence (ISSN: 2292-1648), 2020)
This article highlights the tendency of using prohibited substances by the athletes who participated in Asian Games. The study has utilized Secondary data and data were gathered from the text books and the relevant websites and the database of last eight (8) Asian games held. Descriptive research method was used to analyze the gathered data. Out of all the eight games, the athletes who participated in 1994 Hiroshima games have used the highest number of prohibited substances. Male athletes used prohibited substances more than the female athletes. The most used substance was DHIYDROTESTOSLE. There is a declination of the use of prohibited substances from the first Asian games to the last Asian games.